1995
DOI: 10.1093/jee/88.3.666
|View full text |Cite
|
Sign up to set email alerts
|

Horn Fly (Diptera: Muscidae) Control and Weight Gains of Yearling Beet Cattle

Abstract: Horn fly, Haematobia irritans (L.), populations were controlled on yearling cattle (n = 246) during the grazing season at moderate levels (68% control) with the use of organophosphate- and pyrethroid-impregnated ear tags. Weight gains of treated cattle during the 3-yr period were 17% greater than for untreated cattle. Results from this study demonstrated that yearling cattle of 25 or 50% Brahman, Bos indicus, breeding responded with improved animal performance in Louisiana when moderate horn fly control was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…Fatores biológicos dos bovinos como, por exemplo, raça, cor do pêlo e tamanho da carcaça, podem da mesma forma influenciar e produzir níveis diferenciados de infestações de mosca-dos-chifres (Morgan 1964, Schreiber & Campbell 1986, Steelman et al 1991, Derouen et al 1995, Barros 2001.…”
unclassified
“…Fatores biológicos dos bovinos como, por exemplo, raça, cor do pêlo e tamanho da carcaça, podem da mesma forma influenciar e produzir níveis diferenciados de infestações de mosca-dos-chifres (Morgan 1964, Schreiber & Campbell 1986, Steelman et al 1991, Derouen et al 1995, Barros 2001.…”
unclassified
“…Horn ßy populations on treated heifers were reduced (P Ͻ 0.05), with the overall average ßy counts for the control and treated heifers being 111.0 and 17.8 ßies per side, respectively. Previous studies comparing horn ßy control for yearling beef cattle (Harvey and Brethour,1979, Haufe 1982, DeRouen et al 1995 have reported levels of horn ßy control from 68 to 100%. Overall, the percent reduction in horn ßy population in our study was 84%.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have reported beneÞts of horn ßy control for increasing weight gains of yearling stocker beef cattle (Harvey and Brethour 1979, Haufe 1982, DeRouen et al 1995. These studies, however, did not evaluate the possible effect of horn ßy infestations on the development and reproductive performance of yearling beef replacement heifers.…”
mentioning
confidence: 99%
“…The driving mechanism of the reduction in Iowa is a function of both treatment and fire presence/absence as cows in patch-burned pastures had fewer horn flies than traditionally managed pastures (P = 0.04) and the cows on traditionally managed pastures the unburned year had more horn flies (86 ± 9) than pastures with patchy or complete pasture fires (61 ± 5) (P = 0.02). Furthermore, in burned pastures in Iowa, horn flies were always below the economic threshold of 100 flies per cow side but without any fire horn flies were at the threshold (Gordon et al, 1984;DeRouen et al, 1995). Burning reduced horn flies in Iowa, but in Oklahoma there was no treatment effect (Fig.…”
Section: Horn Fly (H Irritans)mentioning
confidence: 92%